Les conséquences d’un choix résidentiel périurbain sur la mobilité : pratiques et représentations des ménages - Guy Baudelle (Unité Mixte de Recherche 8504 Géographie-cités, 2004)
The study analyzes the consequences of a settlement in the urban fringe on the mobility practices, starting from an investigation near households recently settled close to Rennes (Ille-et-Vilaine, France). This investigation confirms the strong mobility of this type of households and the car modal preponderance, whose the causes are : less journey time, information and organization costs bound to the use of public transport to which is associated by the middle class a social statute loss. The assumption of a low anticipation of the new mobility constraints induced by the residential choice is confirmed. The households recognize their automobile dependence, without we observe a mobility rationalization except some circuits of multi-objects trips or some car-sharing behaviour for the leisures. To reduce car traffic, it thus appears more effective to act upstream by a land and real estate policy supporting a more compact town planning.